Memahami Konsep Perceraian dalam Hukum Keluarga - Ali Imron (BUANA GENDER : Jurnal Studi Gender dan Anak, 2016)
AbstractMarriage is a reunification of human characters.  Husband and wife have the same vision and mission in the marriage, one another as the bonding and unifying factors in establishing a household; there is no subordination of one another.  The husband’s domination over the wife in term of divorce or ‘thalaq’ is very strong and the wife becomes the weak side.  An existence of balance authority between husband and wife in divorce pledge authority is proper to be considered. While the divorce dispute completion is through the court process. It is necessary to reconstruct the ‘thalaq’ conceptual.  First, the divorce must be based on the crisis condition and be the last solution to get out from the household problematic.  Second, the divorce process must be discussed deliberately (syura) which is full of kinship, fairness, and put the common sense forward.  Third, that the waiting period ‘iddah’ prescribed in Islam is more oriented to the divinity and humanity values.  Fourth, prohibition not to go out from the house for mu’taddah is basically not the syari’at objective, but more focused on social moral ethic.Keywords: divorce, marriage, legal consequences AbstrakPerkawinan merupakan reunifikasi sifat kemanusiaan. Suami isteri mempunyai satu visi misi yang sama dalam perkawinan, satu dengan yang lain sebagai unsur perekat dan penyatu dalam membangun rumah tangga, satu dengan lainnya tidak ada subordinasi.Dominasi suami terhadap isteri dalam hal thalak sangat kuat dan isteri menjadi pihak yang lemah. Patut dipertimbangkan adanya kewenangan yang berimbang antara suami isteri dalam hal kewenangan ikrar cerai. Adapun penyelesaian sengketa perceraian tetap melalui proses di pengadilan. Perlu dilakukan upaya untuk merekonstruksi konseptual thalak. Pertama,  perceraian harus dilatarbelakangi oleh kondisi darurat dan merupakan solusi terakhir untuk keluar dari problematika rumah tangga Kedua, proses perceraian harus melalui pembicaraan yang mengedepankan musyawarah (syura) dengan penuh kekeluargaan, adil, dan lebih mengedepankan akal sehat. Ketiga, bahwa `iddah disyariatkan dalam Islam lebih berorientasi pada nilai-nilai ketuhanan dan nilai-nilai kemanusiaan. Keempat, tidak bolehnya mu`taddah keluar rumah pada dasarnya bukanlah tujuan syari`at,  tetapi lebih menyentuh pada etika moral sosial.Kata kunci: perceraian, perkawinan, akibat hukum